China Faced with the Prospect of a Multipolar World (Global Journal of Human-Social Science, 2016)
In the current established political analyses a few ciclehes have been put into circulation such as the USA is the only global superpower the legitimacy of the United States of America s actions on the world stage is self-evident and cannot be questioned it s preferable to have a globalization made under the United States of America because this is an enlightened country and it promotes universal values the Western values promoted by the USA are most certainly better than those of other civilizations and can be extended on a global scale without any issue introducing democracy into countries with a totalitarian political regime will automatically entail their economic prosperity perhaps some of the actions of the United States of America are not good but we shouldn t criticize them because it would not be politically correct etc Our thesis stated and unequivocally argued in the paragraphs below claims instead that an emergent multipolar structure is being set up that the hegemonic legitimacy of the United States of America is questionable and it has already begun its downfall that the USA has entered a pronounced process of relativization of the values it promotes its promoted values that it has begun to significantly lose ground on a moral basis especially after the Wikileaks revelations a loss which will precede and cause future losses of a military political and economic nature
Keywords: china; the US; globalization; multipolar world; arabian spring